PERBANDINGAN METODE RENDERING BASAH DAN EKSTRAKSI PELARUT N-HEKSANA TERHADAP KARAKTERISTIK KIMIA MINYAK IKAN SELAR (Selaroides leptolepis) - Nurfadilah (Jurnal Pengolahan Pangan, 2020)
Fish oil contains nutrients that are good for human growth because generally it contains long-chain unsaturated fatty acids that have double bonds, namely eicosapenta-enoate (EPA), and docose-hexaenoate (DHA). Fish Oil is obtained from the extraction process, namely the process of separating fish oil from the meat. This study aims to determine the comparison of wet rendering methods and n-hexane solvent extraction on the chemical characteristics of selar fish oil (selaroides leptolepis). The method used in this research is descriptive experimental method by comparing the 2 extraction methods that are treated in this study. The extraction method used was the Wet Rendring Extraction Method and N-Hexane Solvent. The extracted fish oil was then characterized by the acid number, saponation number and peroxide number. The saponification number using the wet rendering extraction method (20.63 mg KOH / g) is relatively the same as the solvent extraction method (20.53). The peroxide value in the wet rendering extraction method (29.59 mek / kg) was higher than the n-hexane solvent extraction method (24.77 mek / kg). The acid number in the wet rendering extraction method (70.2 mg KOH / gr) was higher than the solvent extraction method (23.74 mg KOH / gr). Selar fish oil extracted using wet rendering method and n-hexane solvent has low quality